Give seeds a chance? Opportunities and techniques for post‐fire reforestation using tree seeding - Rodman, Kyle C.; Schloegel, Catherine A.; Chapman, Teresa B.; Pineda, Mykael; Chambers, Marin E.; Fornwalt, Paula J.; Stevens, Jens T. (Ecosphere (Washington, D.C), 2025)
Altered fire regimes and post‐fire tree regeneration failures have the potential to drive forest cover losses throughout western North America, but management practices such as active reforestation may help address these challenges. Planting of nursery‐grown tree seedlings currently accounts for the majority of active reforestation in the western United States. Direct tree seeding—an alternative approach that involves dispersing seeds into a project site—is rare but has the potential to supplement planting and increase the pace and scale of reforestation activities, particularly where planting is operationally challenging. In the Southern Rocky Mountains, USA, we used a regionwide spatial analysis to describe (1) the typical locations of post‐fire tree planting and (2) the percentage of severely burned forests that are difficult to access using such treatments. In experimental field trials in two Colorado wildfires, we tracked nearly 40,000 seeds over a one‐year period to test a range of seed enhancement techniques (seed coating, pelleting, and priming) and operational factors (sowing season, microsite characteristics) that might influence direct seeding outcomes. Nearly two‐thirds (63.4%) of post‐fire tree planting activities in this region occurred in severely burned areas, near established roads, and on flatter slopes. About one‐third (32.2%) of all severely burned forests would be challenging to access using tree planting based on current patterns of implementation. In direct seeding field trials, first‐year establishment rates averaged just 0.2% but ranged from 0% to 2.7% across treatments. Untreated seeds had 4× higher establishment rates than those receiving seed enhancement techniques. In the older (20‐year‐old) fire, direct seeding was most effective in sites with bare ground cover; in the more recent (1‐year‐old) fire, direct seeding was most effective in sites where wood mulch was dispersed during post‐fire hillslope stabilization treatments. Direct seeding may help treat vast areas that are difficult to access using tree planting activities. However, increases in seed collection and further exploration of techniques to increase tree establishment rates are needed for this technique to become operationally feasible at broad scales.